An in-depth review of the internal relationships of the EFQM model. Issue 5 (10th August 2015) - Gómez, Joaquín Gómez; Martínez Costa, Micaela; Martínez Lorente, Angel R.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The European Foundation for Quality Management (EFQM) model is widely used as a management tool in companies. Consequently, it is of great importance to understand the relationships within it, and inform managers about appropriate ways to manage events in order to get the desired results in general, and for specific interest groups (stakeholders). The paper aims to discuss these issues. Design/methodology/approach – This paper analyzes the internal relationships of the EFQM model using empirical data from a sample of 199 Spanish companies. Four managers in each company were interviewed, to eliminate single respondent bias. Structural equation modeling is used for the analysis. Findings – The results obtained from the empirical analysis provide evidence of an underlying logic in the EFQM model that does not match the official model. New significant relationships between the enablers and results not considered in the official model have been found. Research limitations/implications – The study focusses on Spanish industrial companies with 50-500 workers and uses a cross-sectional design. Practical implications – Managers should look at the EFQM model as a tool for finding their own way to excellence, but it is not a precise map, because the model may have some problems of definition. Managers should introduce its elements only after deep reflection on its benefit for their company. Originality/value – Despite the previous research on this issue, there is still no clear consensus. Relationships that are not reflected in the theoretical model have been identified.